PENGARUH KEPEMILIKAN MANAJERIAL, LIABILITY, DAN GROWTH TERHADAP FIRM VALUE PADA PERUSAHAAN INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2017 - Lilia, Wirda; siregar, Rosmita Sari; Girsang, Icca Maria (Aksara Public, 2019)
Firm value shows maximizing shareholder wealth through stock prices. Company value is the price paid by prospective buyers if the company is sold. For companies that issue shares in the capital market, the stock price traded on the stock is an indicator of company value. This research was conducted on basic industrial and chemical companies listed on the Indonesia Stock Exchange. The purpose of this study is to determine the effect of managerial ownership, liability, and growth partially and simultaneously on firm value. The population in this study are basic industrial and chemical companies listed on the Indonesia Stock Exchange from the period 2013 to 2017, with a purposive sampling technique obtained as many as 25 companies. The data in this study are secondary data and the hypothesis testing method uses multiple linear regression analysis which produces the equation Y = 0.858-0.002X1 + 0.235X2-0.022X3. The results showed that partially, liability had a significant effect on firm value, while managerial ownership and growth had no significant effect on firm value. Simultaneously, managerial ownership, liability, and growth have a significant effect on firm value.